PENGABDIAN MASYARAKAT MELALUI KULIAH KERJA NYATA (KKN) DI RT 10 DAN RT 12 KELURAHAN CAWANG - Syafitri, Mulyani; Syahdilia, Nella; Nur Anisa, Sarfina; Putri Dewanti, Shafira; Surgawati, Surgawati; Oktaviana, Putri; Tambun, Romauli; Febriana, Sella; Anjarini, Niluh Devi; Purnomo, Frida Octavia; Destiyana, Bunga (Jurnal Mandala Pengabdian Masyarakat, 2024)
Real Work Lecture is a form of community service activity led by students, with a cross-disciplinary and sectoral approach at a certain time and place. The purpose of this community service is to improve the ability to apply knowledge, develop an attitude of responsibility, cooperation, and leadership spirit, increase student understanding of various social, economic, and cultural problems that exist in society, provide solutions and recommendations that can be taken by the government and society to improve community welfare. The methods used in this community service include descriptive, program planning, program implementation, and evaluation. From the results of the pre-test and post-test questionnaire analysis, it can be seen that the respondents' knowledge related to hypertension and uric acid increased after education about these diseases. The conclusion is that the people of RT 10 and RT 12 Cawang Village have an increased understanding of hypertension and gout, this can be seen based on pretest and posttest statistical data conducted when counseling on gout and hypertension.